PRE-SERVICE TEACHING PROGRAM FOR EDUCATING STUDENT- TEACHERS IN MANAGING THEIR CLASS - Titis Sulistyowati; Diah Kurniati (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
This article presents the finding of a study that investigate pre-service English teacher in managing the class when they were teaching in teaching practice program or Pre-Service Teaching Program.  Teaching in a real class is a new experience for the students of Muria Kudus University; however they need to adjust themselves to the teaching environment. They need to prepare some educational knowledge like; classroom management, educational psychology, curriculum development, teaching method etc, in order to be able to organize the lesson well and achieve maximum result. The key of a successful learning is depended on the way teacher organizing the class. In other word the key of a successful language teaching is classroom management.  However each class has different characteristics, so a teacher needs to prepare himself to the students’ learning style.  Maintaining discipline and organizing students can be very frustrating for the student-teachers because they do not only need well understanding about classroom management but they also need to control their performance. The students- teacher or teacher candidates need guidance either from the school teachers or their lecturers; therefore it is also very important to observe their activities in the class to know the improvements which have been done by the teacher.